Analysis of factors affecting medical personnel seeking employment at primary health care institutions: developing human resources for primary health care - Huanhuan Jia; Xihe Yu; Hairui Jiang; Jianxing Yu; Peng Cao; Shang Gao; Panpan Shang; Bayuzhen Qiang (BMC, 2022)
Abstract Background The serious shortage of human resources for primary health care (PHC) is a common issue in health reforms worldwide. China has proposed that it is an effective way to encourage and guide qualified medical personnel to work in primary health care institutions (PHCIs). However, few studies have been conducted on the willingness and influencing factors of medical personnel to seek employment at PHCIs. Methods Based on implicit theory and lexical approach, pre-investigation was conducted to collect the items that influence the medical personnel to seek employment at PHCIs from the perspective of guided objects. Through a three-phase investigation of 1160 doctors in 29 public hospitals in 9 cities, the items were categorized, and a structural equation model was established and verified to explore the interrelationship of influencing factors. Results A total of 6 factors were rotated, including Sense of Gain (SG), Internal Organization Development (IOD), Remuneration and Development (RD), Condition of the City Where the PHCI Is Located (CCPL), Job Responsibilities (JR) and Family Support (FS). The results of the model showed that IOD, RD, JR and FS had a significantly positive effect on the SG. In addition, the FS, RD and JR significantly mediated the relationship between the internal and external environment of PHCIs and SG. The values of the fit index indicated an acceptable-fitting model. Conclusion Family, remuneration, individual development, and job responsibility are closely related to the willingness of medical personnel to seek employment at PHCIs, and the internal and external environment of PHCIs is also an important factor. Therefore, the development of PHC providers can be promoted by paying attention to the family members of medical personnel, establishing a reasonable remuneration system, providing suitable development opportunities, arranging work rationally and improving the internal construction of PHCIs.